A waterproof and corrosion-resistant photoelectric composite cable

By combining the spiral-stranded cable core with aramid yarn in the photoelectric composite cable, and using waterproof and high-temperature insulated polyurethane composite materials and flame-retardant and corrosion-resistant PUR composite materials, the problem of insufficient waterproof and corrosion-resistant performance of the photoelectric composite cable in underwater or underground environments is solved, and a long-term stable use and high-performance photoelectric composite cable is achieved.

CN119252545BActive Publication Date: 2025-03-11HUNAN ZHANTONG INTELLIGENT TECHNOLOGY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411776490.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-11
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

Existing photoelectric composite cables have insufficient waterproof and corrosion resistance in underwater or underground environments, resulting in short service life and poor applicability.

Method used

The structural design includes a cable core, aramid yarn, inner sheath, water barrier layer, anti-corrosion layer and outer sheath. The cable core is combined with the aramid yarn through spiral twisting. The inner sheath is a waterproof and high-temperature insulated polyurethane composite material, and the outer sheath is a flame-retardant and corrosion-resistant PUR composite material.

Benefits of technology

It realizes excellent waterproofness, corrosion resistance, mechanical properties and long-term stability of the optoelectronic composite cable in harsh environments, and its service life can reach 30-40 years.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119252545B_ABST
    Figure CN119252545B_ABST
Patent Text Reader

Abstract

The invention discloses a waterproof and corrosion-resistant optoelectronic composite cable, belonging to the technical field of communication cables; the waterproof and corrosion-resistant optoelectronic composite cable of the invention comprises a cable core composed of an optical unit and an electrical unit, aramid yarn, an inner protective layer, a water-blocking layer, an anti-corrosion layer and an outer sheath, wherein the optical unit comprises an optical fiber and a protective sheath outside the optical fiber, and the electrical unit comprises a conductor and an insulating layer outside the conductor; the aramid yarn is spirally twisted with the cable core, and an inner protective layer is extruded outside the inner protective layer, a water-blocking layer is wrapped outside the inner protective layer, an anti-corrosion layer is coated outside the water-blocking layer, and an outer sheath is coated outside the anti-corrosion layer; the inner protective layer is a waterproof and high-temperature resistant insulating polyurethane composite material; the outer sheath is a flame-retardant and corrosion-resistant PUR composite material; the waterproof and corrosion-resistant optoelectronic composite cable of the invention has a simple structure, high strength and high toughness, and has excellent waterproofness, corrosion resistance, aging resistance, high temperature resistance, wear resistance and flame retardancy, and still maintains relatively good use performance and a long service life in harsh environments such as underwater or underground.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of communication cables, and in particular relates to a waterproof and corrosion-resistant optoelectronic composite cable. Background Art

[0002] With the development of communication optical cables, the application of optoelectronic composite cables is very extensive. my country has a vast territory, with high mountains, rivers and lakes; the climate is changeable, with severe winter and high cold, high temperature and humidity, wind and sun, ant invasion and bird pecking. In order to adapt to the requirements of laying methods and operating environments, the structure of optical cables is constantly developing. For special optoelectronic composite cables for power equipment that need to use electricity as power, such as lifting hydraulic grab beams and silt removers, it is often necessary to wind the cable on a drum, and one end of the cable is immersed in water together with the lifting hydraulic grab beam and silt remover. This requires the optoelectronic composite cable to have certain waterproof and corrosion resistance. However, in the prior art, in order to ensure the strength of underwater optoelectronic composite cables, steel pipes are generally installed on the outer shell of the cable, and the steel pipes are used as protective sleeves. However, the steel pipes are not flexible, so the cables with steel pipe sleeves cannot be wound on the drum, and cannot be used at all. In addition, the optoelectronic composite cables in the prior art are often eroded by water and moisture because they are underground for a long time, and the waterproof and corrosion-resistant effects are not very good, and the applicability is poor.

[0003] The existing optoelectronic composite cable is composed of optical fiber, cable core and protective layer. In the conventional round optoelectronic composite cable, the cable core is twisted around the central reinforcement by optical fiber coated with a protective layer, conductor coated with an insulating layer and filling rope, and the cable core is covered with a sheath to ensure that the cable is not corroded. In the current optoelectronic composite cable, the conventional sheath materials are polyolefin sheath, polyvinyl chloride sheath and polyurethane sheath. The polyolefin sheath has good mechanical strength and chemical resistance, and after cross-linking modification, the working temperature can reach 150℃, the water absorption is small, and the electrical insulation is excellent, but the heat aging resistance and corrosion resistance are poor, and the low temperature resistance and wear resistance are general; the polyurethane sheath has high strength and toughness, and has excellent wear resistance, high temperature resistance, flame retardancy and chemical corrosion resistance, but it is brittle and easy to break, has poor heat resistance under high temperature conditions, and is easily corroded by chemicals such as methanol, water, ultraviolet rays, concentrated acid and alkali, which affects the service life; the polyvinyl chloride sheath has low cost, high strength and toughness, and has excellent flame retardancy, waterproofness and chemical corrosion resistance, but it is easy to age, has poor wear resistance and is not environmentally friendly. Therefore, it is necessary to develop a waterproof and corrosion-resistant optoelectronic composite cable with high strength, good toughness, high temperature resistance and anti-aging, so that it can solve the problem of waterproof and corrosion resistance while also making the comprehensive performance of the optoelectronic composite cable excellent.

[0004] Invention patent CN201810859540.3 discloses a calendering-grade high-temperature resistant thermoplastic polyurethane elastomer, whose components are: isocyanate, polymer polyol, small molecule diol, diepoxysiloxane, catalyst, PE wax, antioxidant and other additives, which improves the heat resistance of TPU so that it still has better processing performance at high temperature. However, the thermoplastic polyurethane elastomer also has better moisture permeability. Therefore, the TPU is not suitable for protecting the internal cable core, that is, it is not suitable for use as the outer sheath of the cable. Invention patent CN201310401119.5 discloses a highly flexible insulating sheath material for transformers, which comprises the following components: acrylic rubber, polyurethane rubber, nylon 66, dioctyl epoxytetrahydrophthalate, dioctyl nylonate, chlorinated paraffin, aluminum hydroxide, zinc borate, carbon black N660, magnesium carbonate, quartz powder, nano fluorite powder and other raw materials. It has good flexibility, high toughness, good tensile aging resistance, can withstand long-term bending movement, has extremely excellent tensile properties, and also has excellent heat resistance, weather resistance, acid and alkali corrosion resistance, electrical insulation, tear strength and other properties. However, the insulating sheath material has average waterproofness and average corrosion resistance to some special chemicals (such as methanol, concentrated acid and alkali, etc.), which affects the service life and use environment of the sheath material. Summary of the invention

[0005] The main purpose of the present invention is to provide a waterproof and corrosion-resistant optoelectronic composite cable, which has a simple structure, is easy to manufacture, has high strength and high toughness, and has excellent waterproofness, corrosion resistance, aging resistance, high temperature resistance, wear resistance and flame retardancy, and can still maintain excellent performance and a long service life in harsh environments such as underwater or underground.

[0006] In order to achieve the purpose of the present invention, the present invention provides a waterproof and corrosion-resistant optoelectronic composite cable, comprising a cable core, aramid yarn, an inner sheath, a water-blocking layer and an outer sheath, wherein the cable core comprises an optical unit and an electrical unit, wherein the optical unit comprises an optical fiber and a protective sheath wrapped around the outside of the optical fiber, and the electrical unit comprises a conductor and an insulating layer wrapped around the outside of the conductor; the aramid yarn is spirally twisted with the cable core and extruded with an inner sheath, the inner sheath is wrapped with a water-blocking layer, the water-blocking layer is coated with an anti-corrosion layer, and the anti-corrosion layer is coated with an outer sheath;

[0007] The protective cover comprises a first protective cover, an aramid braided layer and a second protective cover, wherein the optical fiber is wrapped in the first protective cover, the aramid braided layer is coated on the outside of the first protective cover, and the aramid braided layer is coated on the outside of the second protective cover.

[0008] The inner protective layer is a waterproof and high temperature resistant insulating polyurethane composite material;

[0009] The waterproof and high temperature resistant insulating polyurethane composite material is made of the following raw materials in parts by mass: 50-70 parts of POSS end-capped polyurethane resin, 15-30 parts of acrylic rubber, 5-10 parts of ethylene-vinyl acetate copolymer, 0.5-3 parts of silane coupling agent, 5-10 parts of first flame retardant, 2.5-4 parts of first antioxidant, 0.8-1.5 parts of first anti-aging agent and 0.5-1.5 parts of first lubricant.

[0010] The outer sheath is made of flame-retardant and corrosion-resistant PUR composite material;

[0011] The flame-retardant and corrosion-resistant PUR composite material is made of the following raw materials in parts by mass: 60-80 parts of polycarbonate waterborne polyurethane resin, 20-40 parts of modified polyurethane acrylate, 5-10 parts of silicone resin microspheres (i.e., polymethylsilsesquioxane), 10-20 parts of maleic anhydride grafted TPU, 3-5 parts of pentaerythritol triallyl ether, 20-40 parts of a second flame retardant, 4-6 parts of a smoke suppressant, 2-5 parts of a second antioxidant, 1.2-1.8 parts of a second anti-aging agent, and 1.5-2.5 parts of a second lubricant.

[0012] Furthermore, the optical unit and the electrical unit are arranged in a spiral twisted manner.

[0013] Further, the preparation method of the POSS terminated polyurethane resin comprises the following steps:

[0014] S1. Place carbon dioxide-based polyol and propylene carbonate in a container, keep the temperature at 120±5°C under vacuum for 1-2h, then release the vacuum and introduce nitrogen, cool to 80±5°C, add isophorone diisocyanate, keep the temperature for 1-2h, then add an organic tin catalyst, and heat to 100±5°C for 2-5h to obtain a polyurethane prepolymer;

[0015] S2. Add 4,4'-methylenebis(2-ethyl)aniline to the above polyurethane prepolymer, cool to 90±5°C and continue the reaction for 2-4h, then cool to 70±5°C, add cage-type polysilsesquioxane-hydroxyl group and keep warm for 2-5h, cool naturally to room temperature, and evacuate for 10±2min to obtain POSS-terminated polyurethane resin.

[0016] Furthermore, the carbon dioxide-based polyol has a hydroxyl value of 34-59 mgKOH / g and a functionality of 2-3.

[0017] Further, the molar ratio of -NCO in the isophorone diisocyanate to -OH in the carbon dioxide-based polyol is (2.5-3.5):1;

[0018] The amount of propylene carbonate added is 15-30% of the mass of the carbon dioxide-based polyol;

[0019] The amount of the organotin catalyst added is 0.04-0.10% of the total mass of the isophorone diisocyanate and the carbon dioxide-based polyol;

[0020] The amount of 4,4'-methylenebis(2-ethyl)aniline added is 1.5-3.2% of the total mass of the isophorone diisocyanate and the carbon dioxide-based polyol;

[0021] The mass ratio of the cage-type polysilsesquioxane-alcoholic hydroxyl group to the isophorone diisocyanate is (0.2-0.4):1.

[0022] Furthermore, the silane coupling agent is any one or more of vinyltrimethoxysilane, aminopropyltriethoxysilane or isobutyltriethoxysilane;

[0023] The first flame retardant is any one or more of magnesium hydroxide, aluminum hydroxide, antimony trioxide, zinc borate or polyphosphate;

[0024] The first antioxidant is any one or more of antioxidant 1010, antioxidant 168 or antioxidant B900;

[0025] The first anti-aging agent is any one of UV531, UV1300 or UV1240;

[0026] The first lubricant is any one of zinc stearate, magnesium stearate or calcium stearate.

[0027] Furthermore, the second flame retardant is composed of ammonium polyphosphate AP417, magnesium hydroxide and aluminum hydroxide in a mass ratio of (1-1.5): (1.5-3): (1.5-3);

[0028] The smoke suppressant is a halogen-free flame retardant carbon-forming agent FR501;

[0029] The second antioxidant is composed of antioxidant 1135 and antioxidant 168 in a mass ratio of 2:1;

[0030] The second anti-aging agent is composed of UV531 and UV119 in a mass ratio of 1:3;

[0031] The second lubricant is one or more of calcium stearate, zinc stearate, organic montmorillonite or hydrogenated silicone oil.

[0032] Furthermore, the insulating layer is 90-degree insulation grade soft polyvinyl chloride plastic;

[0033] The water-blocking layer is a halogen-free and non-corrosive polyester non-woven water-blocking tape;

[0034] The anti-corrosion layer is a waterproof polyurethane anti-corrosion tape, on which a siloxane coating is applied, and the thickness of the siloxane coating is 10-20% of the thickness of the waterproof polyurethane anti-corrosion tape;

[0035] The first protective cover and the second protective cover are both made of LSZH cable material.

[0036] Furthermore, the silicone coating is composed of raw materials of polydimethylsiloxane, amino silicone oil, triethoxysilane and n-hexane in a mass ratio of (5-7): (2-3): (0.1-0.2): (1-2).

[0037] The present invention has achieved the following beneficial effects:

[0038] The optoelectronic composite cable of the present invention is prepared by twisting an optical unit and an electrical unit together with aramid yarn in a spiral twisting manner, and then arranging an inner protective layer, a water-blocking layer, an anti-corrosion layer and an outer sheath from the inside to the outside. It can meet the requirements of waterproof and corrosion resistance in harsh environments such as underwater or underground, and also has excellent mechanical properties, wear resistance, weather resistance, aging resistance and high and low temperature resistance. The combustion grade of the optoelectronic composite cable can reach B1 grade.

[0039] The base materials of the inner protective layer, the anti-corrosion layer and the outer protective layer of the present invention are all polyurethane, which is halogen-free and environmentally friendly. It can ensure that the optoelectronic composite cable still has excellent mechanical strength, electrical insulation, waterproofness, corrosion resistance, aging resistance and high and low temperature stability in harsh environments containing water, corrosive substances, etc., and can still maintain good communication effects after long-term use, with a service life of up to 30-40 years.

[0040] The waterproof and corrosion-resistant optoelectronic composite cable prepared by the invention has a smooth surface, a simple structure, is easy to manufacture, has excellent waterproof and corrosion-resistant performance, a wide range of applications and is low in cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 It is a schematic structural diagram of an embodiment of the waterproof and corrosion-resistant optoelectronic composite cable of the present invention.

[0042] Figure symbols: 1. conductor; 2. optical fiber; 3. insulation layer; 4. first protective cover; 5. aramid braided layer; 6. second protective cover; 7. aramid yarn; 8. inner protective layer; 9. water-blocking layer; 10. anti-corrosion layer; 11. outer sheath. DETAILED DESCRIPTION

[0043] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0044] like Figure 1 As shown, the present invention provides a waterproof and corrosion-resistant optoelectronic composite cable, comprising a cable core, an aramid yarn 7, an inner protective layer 8, a water-blocking layer 9, an anti-corrosion layer 10 and an outer sheath 11. The aramid yarn 7 and the cable core are laid out in a spiral twisting manner, and then the inner protective layer 8 is extruded around the twisted aramid yarn 7 and the cable core, the water-blocking layer 9 is wrapped around the inner protective layer 8, the water-blocking layer 9 is coated with the anti-corrosion layer 10, and the anti-corrosion layer 10 is coated with the outer sheath 11.

[0045] Preferably, the aramid yarn 7 is made of aramid with a fineness of ≥10000 dtex and imported super-resistant aramid with a tensile modulus greater than 120 GPa. The present invention uses aramid yarn 7 as a reinforcement to protect the cable core, which can ensure inherent stability, extremely low thermal shrinkage, low creep and extremely high glass transition temperature at higher temperatures, and also has higher corrosion resistance, and has strong chemical resistance except for strong acids and alkalis.

[0046] Specifically, in the embodiment of the present invention, the aramid yarn 7 selected is DuPont Kevlar aramid with a specification of 1500D and an elongation modulus of up to 131 GPa.

[0047] The present invention arranges the cable core and the aramid yarn 7 in a spiral twisted manner, thereby improving the tensile strength of the cable core, improving the mechanical strength of the optoelectronic composite cable, and reducing the probability of the optical fiber 2 being crushed or broken.

[0048] The cable core is formed by spirally twisting one optical unit and two electrical units (the number of optical units and electrical units is freely selected according to actual conditions). The optical unit includes an optical fiber 2, a first protective sheath 4, an aramid braided layer 5 and a second protective sheath 6 from the inside to the outside, that is, the optical fiber 2 is wrapped in the first protective sheath 4, the aramid braided layer 5 is coated on the outside of the first protective sheath 4, and the aramid braided layer 5 is coated on the outside of the second protective sheath 6.

[0049] Preferably, the conductor 1 is a copper conductor 1, and the optical fiber 2 is a G657A2 bending-resistant optical fiber 2. The aramid braided layer 5 is woven with imported super-resistant aramid (i.e., the DuPont Kevlar aramid mentioned above); the optical unit and the electrical unit are twisted spirally to reduce electromagnetic interference and improve signal transmission quality; the outer layer of the optical fiber 2 is wrapped with a super-resistant aramid reinforcement to ensure that it can remain invariant under extreme environmental conditions and ensure that the optical fiber 2 can operate stably.

[0050] Preferably, the first protective cover 4 and the second protective cover 6 are both formed by extrusion of LSZH cable material (i.e., low-smoke halogen-free flame-retardant cable material), which is halogen-free and environmentally friendly, and can effectively protect the optical fiber 2 from being easily damaged during bending or stretching, while ensuring that the optoelectronic composite cable has good communication capabilities and is not easily interfered with, and the present invention has excellent insulation and flame retardancy, thereby improving the mechanical properties, aging resistance, corrosion resistance and temperature resistance level of the optoelectronic composite cable.

[0051] Specifically, in the embodiment of the present invention, the selected LSZH cable material is a low-smoke halogen-free TPU cable material, 1154-D-10K-FFC from BASF of Germany.

[0052] Preferably, the insulating layer 3 is a 90-degree insulation grade soft polyvinyl chloride plastic. The insulating layer 3 is used to protect the electrical properties of the conductor 1, ensure the flexibility, insulation and flame retardancy of the electrical unit, avoid the optical unit communication being affected, and improve the mechanical properties, corrosion resistance and high temperature resistance of the optoelectronic composite cable.

[0053] Specifically, in the embodiment of the present invention, the 90-degree insulation grade soft polyvinyl chloride plastic is selected from the (J-90) 90-degree insulation grade soft polyvinyl chloride plastic of Xinzhongcheng Cable.

[0054] Preferably, the inner protective layer 8 is a waterproof and high temperature resistant insulating polyurethane composite material, which can significantly improve the toughness, waterproofness and high temperature resistance of the optoelectronic composite cable of the present invention, and ensure that the present invention has excellent mechanical strength, corrosion resistance, electrical insulation, flame retardancy, low temperature resistance, aging resistance and other properties, so that it can still be used for a long time in harsh environments.

[0055] The waterproof and high temperature resistant insulating polyurethane composite material is made of the following raw materials in parts by mass: 50-70 parts of POSS end-capped polyurethane resin, 15-30 parts of acrylic rubber, 5-10 parts of ethylene-vinyl acetate copolymer, 0.5-3 parts of silane coupling agent, 5-10 parts of first flame retardant, 2.5-4 parts of first antioxidant, 0.8-1.5 parts of first anti-aging agent, and 0.5-1.5 parts of first lubricant. The waterproof and high temperature resistant insulating polyurethane composite material of the present invention uses POSS end-capped polyurethane resin as a matrix, which improves the toughness (protecting the internal cable core), waterproofness and high temperature resistance of the present invention, and at the same time ensures that the present invention has excellent comprehensive properties such as electrical insulation, mechanical strength, corrosion resistance, flame retardancy and low temperature resistance; the addition of acrylic rubber significantly improves the high temperature resistance, corrosion resistance, waterproofness, aging resistance and other properties of the inner sheath 8, and further improves the high temperature service life of the optoelectronic composite cable in a water environment; the addition of ethylene-vinyl acetate copolymer has good compatibility with the POSS end-capped polyurethane resin, further improves the toughness and chemical stability of the inner sheath 8, and can ensure that the inner sheath 8 reaches the mechanical and electrical properties required by the present invention, and improves the tensile strength, waterproofness and corrosion resistance of the present invention. The raw material combination and proportion of the waterproof and high temperature resistant insulating polyurethane composite material ensure that the present invention has good mechanical strength, toughness, waterproofness, high temperature resistance and combustion performance, and interacts with each component structure of the optoelectronic composite cable to ensure that it has excellent comprehensive performance.

[0056] Specifically, in the embodiment of the present invention, the acrylic rubber is selected from DuPont's ethylene acrylic rubber, model AEM.

[0057] In the embodiment of the present invention, the ethylene-vinyl acetate copolymer is selected from DuPont's ethylene-vinyl acetate, model PV1300Z.

[0058] Preferably, the preparation method of POSS end-capped polyurethane resin is:

[0059] 1 kg of carbon dioxide-based polyol and 240 g of propylene carbonate were placed in a container, kept warm at 120°C for 2 hours, then the vacuum was released and nitrogen was introduced, cooled to 80°C, 325 g of isophorone diisocyanate was added, kept warm for 2 hours, and then 0.8 g of organic tin catalyst was added, and the temperature was raised to 100°C for reaction for 4 hours to obtain a polyurethane prepolymer; 37 g of 4,4'-methylenebis(2-ethyl)aniline was added to the polyurethane prepolymer, the temperature was lowered to 90°C and the reaction was continued for 3 hours, then the temperature was lowered to 70°C, 98 g of cage-type polysilsesquioxane-hydroxyl group was added, kept warm for 4 hours, naturally cooled to room temperature, and vacuumed for 10 minutes to obtain a POSS-terminated polyurethane resin.

[0060] Preferably, the carbon dioxide based polyol has a hydroxyl value of 34-59 mgKOH / g and a functionality of 2-3.

[0061] Specifically, the hydroxyl value of the carbon dioxide-based polyol in the embodiment of the present invention is 56 mgKOH / g, the functionality is 2, and the molecular weight is 2050. The carbon dioxide-based polyol and isophorone diisocyanate are selected as the main raw materials to prepare the polyurethane prepolymer, which not only improves the mechanical strength and toughness of the POSS blocked polyurethane resin, but also improves the water resistance, chemical corrosion resistance and high temperature resistance of the POSS blocked polyurethane resin, thereby improving production efficiency.

[0062] The present invention uses cage-type polysilsesquioxane-alcoholic hydroxyl groups to perform end-capping treatment on polyurethane, thereby improving the waterproofness and high temperature resistance of the inner protective layer 8, while increasing the compatibility between polyurethane and components such as acrylic rubber and the first flame retardant, improving the bonding force between the polyurethane and the cable core, making it difficult for the inner protective layer 8 to fall off from the cable core, and improving the toughness, wear resistance and corrosion resistance of the inner protective layer 8. In the embodiment of the present invention, the cage-type polysilsesquioxane-alcoholic hydroxyl group is selected from Qiyue Biological.

[0063] Preferably, the silane coupling agent is any one or more of vinyltrimethoxysilane, aminopropyltriethoxysilane or isobutyltriethoxysilane, which can improve the bonding force between the organic and inorganic components in the POSS terminated polyurethane resin, thereby improving the mechanical strength, water resistance and high temperature resistance of the inner protective layer 8.

[0064] Specifically, in the embodiment of the present invention, the silane coupling agent is aminopropyltriethoxysilane.

[0065] Preferably, the first flame retardant is any one or more of magnesium hydroxide, aluminum hydroxide, antimony trioxide, zinc borate or polyphosphate.

[0066] Specifically, in the embodiment of the present invention, the first flame retardant is composed of ammonium polyphosphate (selected from Clariant ExolitAP417), aluminum hydroxide and zinc borate in a mass ratio of 3:1:2. The three components of the flame retardant combination cooperate with each other to significantly improve the flame retardancy, corrosion resistance and water resistance of the present invention, and ensure that the present invention has good mechanical properties, high temperature resistance and electrical properties.

[0067] Preferably, the first antioxidant is any one or more of antioxidant 1010, antioxidant 168 or antioxidant B900.

[0068] Specifically, in the embodiment of the present invention, the first antioxidant is composed of antioxidant B900 and antioxidant 168 in a mass ratio of 1:1, which improves the heat-oxidative aging resistance of the waterproof and high-temperature resistant insulating polyurethane composite material and has high thermal stability.

[0069] Preferably, the first anti-aging agent is any one of UV531, UV1300 or UV1240.

[0070] Specifically, in the embodiment of the present invention, the first anti-aging agent is UV531.

[0071] Preferably, the first lubricant is any one of zinc stearate, magnesium stearate or calcium stearate.

[0072] Specifically, in the embodiment of the present invention, the lubricant is a composition of zinc stearate and calcium stearate in a mass ratio of 2:1, which improves the processing fluidity and dimensional stability of the waterproof and high temperature resistant insulating polyurethane composite material.

[0073] Preferably, the water-blocking layer 9 is a halogen-free and non-corrosive polyester non-woven water-blocking tape, which is overlapped and wrapped around the inner protective layer 8 with an overlap rate of 45-50%.

[0074] Specifically, in order to further ensure the waterproof performance of the present invention, the water-blocking layer 9 in the embodiment of the present invention uses the PET non-woven water-wrapped tape of Ruibo Nonwoven Technology, model CB-50, which adopts double-layer overlapping wrapping and the overlap rate is 50%. The use of the water-blocking tape selected in the embodiment of the present invention not only improves the water-blocking property of the optoelectronic composite cable of the present invention, but also improves the impact resistance, folding resistance, chemical corrosion resistance and high and low temperature resistance of the present invention, and further ensures the electrical insulation and use effect of the present invention.

[0075] Preferably, the anti-corrosion layer 10 is a waterproof polyurethane anti-corrosion tape, and the waterproof polyurethane anti-corrosion tape is coated with a siloxane coating (not shown in the figure), and the thickness of the siloxane coating is 10-20% of the thickness of the waterproof polyurethane anti-corrosion tape.

[0076] Specifically, the waterproof polyurethane anti-corrosion belt in the embodiment of the present invention is made of TPU1049 from Bayer of Germany. The siloxane coating on the surface of the waterproof polyurethane anti-corrosion belt can not only ensure that it has good chemical corrosion resistance, but also enable the siloxane coating coated thereon to achieve a long-term waterproof effect, making it less susceptible to corrosion in a water environment, thereby enabling the present invention to have a long-term waterproof and anti-corrosion effect. At the same time, it also improves the flame retardancy and high and low temperature resistance of the present invention.

[0077] Preferably, the silicone coating is prepared by mixing polydimethylsiloxane, aminosilicone oil, triethoxysilane and n-hexane in a mass ratio of (5-7):(2-3):(0.1-0.2):(1-2).

[0078] Specifically, the siloxane coating in the embodiment of the present invention is a mixture of polydimethylsiloxane, aminosilicone oil, triethoxysilane and n-hexane in a mass ratio of 6:2:0.2:2. The use of polydimethylsiloxane and aminosilicone oil not only improves the chemical corrosion resistance of the product, but also increases the life of the product in harsh environments. Even if it is used for a long time in the presence of water or chemical reagents, the present invention can still ensure excellent comprehensive performance.

[0079] Preferably, the outer sheath 11 is a flame retardant and corrosion resistant PUR composite material with an oxygen index ≥ 35, and has excellent mechanical properties, flame retardancy, water resistance, high temperature resistance, chemical corrosion resistance, wear resistance, aging resistance and electrical insulation.

[0080] The flame retardant and corrosion resistant PUR composite material is made of the following raw materials in parts by mass: 60-80 parts of polycarbonate type waterborne polyurethane resin, 20-40 parts of modified polyurethane acrylate, 5-10 parts of silicone resin microspheres (i.e., polymethylsilsesquioxane), 10-20 parts of maleic anhydride grafted TPU, 3-5 parts of pentaerythritol triallyl ether, 20-40 parts of the second flame retardant, 4-6 parts of smoke suppressant, 2-5 parts of the second antioxidant, 1.2-1.8 parts of the second anti-aging agent, and 1.5-2.5 parts of the second lubricant. The raw materials of the flame retardant and corrosion resistant PUR composite material are combined and appropriately proportioned to ensure that the present invention has good mechanical strength, waterproofness, high temperature resistance, corrosion resistance, aging resistance and flame retardancy, and has good bonding strength with the anti-corrosion layer 10, ensuring that the present invention has excellent comprehensive performance.

[0081] In order to ensure that the flame-retardant and corrosion-resistant PUR composite material of the present invention has excellent mechanical properties, water resistance, flame retardancy and corrosion resistance, the present invention preferably selects the polycarbonate type waterborne polyurethane resin from Japan Aidi Co., Ltd. BONTIGHTER-HUX-564, with a particle size of 0.2 μm; the modified polyurethane acrylate is selected from the modified polyurethane acrylate of Sunbright Biotech, model WDS-2210. The polycarbonate type waterborne polyurethane resin and the modified polyurethane acrylate are selected in an appropriate proportion combination to ensure that the outer sheath 11 is easy to process, has better mechanical properties and ductility, and significantly improves the water resistance, flame retardancy, corrosion resistance and high temperature resistance of the outer sheath 11, while ensuring that the present invention has excellent electrical insulation, mechanical strength, low temperature resistance and other comprehensive properties.

[0082] The addition of silicone resin microspheres to the flame retardant and corrosion resistant PUR composite material of the present invention improves the processing fluidity of the flame retardant and corrosion resistant PUR composite material, and makes the components in the PUR composite material evenly dispersed, significantly improving the waterproofness, chemical corrosion resistance, high temperature stability, weather resistance, flame retardancy, etc. of the outer protective layer; the silicone resin microspheres are used in combination with pentaerythritol triallyl ether to improve the bonding force and crosslinking density between the components in the flame retardant and corrosion resistant PUR composite material, thereby improving the mechanical strength, high temperature resistance and flame retardancy of the outer sheath 11. In this embodiment, the silicone resin microspheres are selected from polymethylsilsesquioxane of Batai New Materials, model BT-9273.

[0083] Preferably, the maleic anhydride grafted TPU is selected from BIORICH of Germany, which improves the compatibility of the components in the flame retardant and corrosion resistant PUR composite material, improves the toughness and mechanical strength of the present invention, and can ensure that the present invention has excellent comprehensive performance.

[0084] Preferably, the second flame retardant is composed of ammonium polyphosphate AP417, magnesium hydroxide and aluminum hydroxide in a mass ratio of (1-1.5): (1.5-3): (1.5-3). The halogen-free flame retardant made by using this combination ratio not only has excellent flame retardancy, but also ensures that the flame-retardant and corrosion-resistant PUR composite material has excellent mechanical strength, high temperature resistance and processing performance.

[0085] Specifically, the second flame retardant selected in the embodiment of the present invention is composed of ammonium polyphosphate AP417, magnesium hydroxide and aluminum hydroxide in a mass ratio of 1:2:2.

[0086] Preferably, the smoke suppressant is a halogen-free flame retardant carbon-forming agent FR501, which is used in combination with the second flame retardant to ensure that the present invention has excellent low-smoke flame retardant properties, can form a non-drip hard shell-like substance during the combustion process, and can also ensure that the flame retardant and corrosion-resistant PUR composite material has excellent comprehensive properties, such as mechanical strength, waterproofness, corrosion resistance, etc.

[0087] Preferably, the second antioxidant is composed of antioxidant 1135 and antioxidant 168 in a mass ratio of 2:1, which improves the heat-oxidative aging resistance of the flame-retardant and corrosion-resistant PUR composite material, is not easy to change color, and extends the service life of the present invention.

[0088] Preferably, the second anti-aging agent is composed of UV531 and UV119 in a mass ratio of 1:3.

[0089] Preferably, the second lubricant is one or more of calcium stearate, zinc stearate, organic montmorillonite or hydrogenated silicone oil.

[0090] Specifically, in the embodiment of the present invention, the second lubricant is zinc stearate and organic montmorillonite in a mass ratio of 2:3, which improves the processing fluidity and dimensional stability of the waterproof and high temperature resistant insulating polyurethane composite material.

[0091] Preferably, the outer diameter of the optical unit of the present invention is 4.0±0.2mm, and the thickness of the protective sleeve is 1.5±0.2mm; the outer diameter of the electrical unit is 3.0±0.2mm, and the thickness of the insulating layer 3 is 1.0±0.1mm; the aramid yarn 7 uses aramid with a fineness of 10000dtex; the wall thickness of the inner protective layer 8 is 0.8±0.1mm; the wall thickness of the water-blocking layer 9 is 0.6±0.1mm; the wall thickness of the anticorrosive layer 10 is 1.2±0.2mm; and the wall thickness of the outer sheath 11 is 2.0±0.2mm. The structural setting of the present invention can ensure the product quality while ensuring its excellent comprehensive performance.

[0092] The present invention also provides a preparation process of a waterproof and corrosion-resistant optoelectronic composite cable, and the specific process flow is as follows:

[0093] S1. Extruding 90-degree insulation grade soft polyvinyl chloride plastic onto the copper conductor 1 through an extruder to form an electrical unit.

[0094] S2. Extrude low-smoke halogen-free TPU cable material onto the optical fiber 2 to form a first protective cover 4; then wrap an aramid braided tape around the first protective cover 4 to form an aramid braided layer 5; extrude low-smoke halogen-free TPU cable material onto the aramid braided layer 5 through an extruder to form a second protective cover 6, that is, the first protective cover 4, the aramid braided layer 5 and the second protective cover 6 constitute the protective cover of the optical fiber 2, and the optical fiber 2 and the protective cover constitute the optical fiber 2 unit.

[0095] S3. Weigh the raw materials in the above-mentioned waterproof, high-temperature resistant and insulating polyurethane composite material according to their mass fractions, add them into a high-speed mixer, mix them at 560r / min and 80-90℃ for 10-15min, cool them to below 60℃, and then convey them to a twin-screw extruder for granulation to obtain a waterproof, high-temperature resistant and insulating polyurethane composite material; twist the optical unit and the electrical unit into a whole with the aramid yarn 7 by spiral twisting, and then use an extruder at a temperature of 170-200℃ to extrude and coat the above-mentioned polyolefin composite shielding material on the twisted cable core with aramid yarn 7 to form an inner protective layer 8.

[0096] S4. Wrap the halogen-free and non-corrosive polyester non-woven water-blocking tape around the inner protective layer 8 to form a water-blocking layer 9.

[0097] S5. Extruding TPU1049 onto the water-blocking layer 9 through an extruder, and then coating the surface away from the water-blocking layer 9 with a siloxane coating (i.e., the raw materials of the above-mentioned siloxane coating are weighed according to the required ratio and mixed evenly), and curing to obtain a siloxane coating, and the thickness of the siloxane coating is 10% of the thickness of the TPU1049 extruded layer, thereby forming an anti-corrosion layer 10 with a siloxane coating.

[0098] S6. Weigh the raw materials in the above-mentioned flame retardant and corrosion-resistant PUR composite material according to their mass fractions, add them into a high-speed mixer, mix them at 560r / min and 110-120℃ for 20 minutes, cool them to below 60℃, and then convey them to a twin-screw extruder for granulation to obtain a flame retardant and corrosion-resistant PUR composite material; then use an extruder at a temperature of 170-200℃ to extrude the above-prepared flame retardant and corrosion-resistant PUR composite material onto the anti-corrosion layer 10 to form an outer sheath 11.

[0099] The waterproof and corrosion-resistant optoelectronic composite cable of the present invention is described below in conjunction with specific embodiments.

[0100] Inner sheath: waterproof and high temperature resistant insulating polyurethane composite material.

[0101] Example 1, a waterproof, high temperature resistant insulating polyurethane composite material is made of the following raw materials in parts by mass: 65 parts of POSS end-capped polyurethane resin, 27 parts of butyl acrylate rubber, 8 parts of ethylene-vinyl acetate copolymer, 2.3 parts of silane coupling agent, 8.5 parts of a first flame retardant, 3.2 parts of a first antioxidant, 1.2 parts of a first anti-aging agent, and 0.8 parts of a first lubricant.

[0102] The raw materials, raw material models and preparation process of the POSS terminated polyurethane resin are all described in the above specific implementation manner. Please refer to the above description for details.

[0103] After testing, the tensile strength of Example 1 is 41.5 MPa, the elongation at break is 856.8%, the heat deformation temperature is 125°C, the water absorption is 0.15%, and the oxygen index is 35.4.

[0104] Comparative Example 1: The polyurethane composite material of Comparative Example 1 has the same raw materials and preparation method as those in Example 1, with specific reference to Example 1, except that in Comparative Example 1, cage-type polysilsesquioxane-hydroxyl groups are not used for end-capping, that is, cage-type polysilsesquioxane-hydroxyl groups are not added, and 4,4'-methylenebis(2-ethyl)aniline is added to the polyurethane prepolymer, the temperature is reduced to 90°C and the reaction is continued for 4 hours, naturally cooled to room temperature, and vacuumed for 10 minutes to obtain a polyurethane resin.

[0105] After testing, the tensile strength of Comparative Example 1 was 32.1 MPa, the elongation at break was 625.4%, the heat deformation temperature was 104°C, the water absorption was 0.52%, and the oxygen index was 32.8.

[0106] Comparative Example 2: The polyurethane composite material of Comparative Example 2 has the same raw materials and preparation method as those in Example 1, and specific reference is made to Example 1. The difference is that in this Comparative Example 2, terminal hydroxyl polydimethylsiloxane (selected from Dow Corning's hydroxyl silicone oil, model PMX-0156) is used instead of cage-type polysilsesquioxane-alcohol hydroxyl group.

[0107] After testing, the tensile strength of Comparative Example 2 was 36.5 MPa, the elongation at break was 752.8%, the heat deformation temperature was 108°C, the water absorption was 0.34%, and the oxygen index was 35.1.

[0108] Comparative Example 3, the polyurethane composite material of Comparative Example 3 has the same raw materials and preparation method as those in Example 1, and specific reference is made to Example 1. The difference is that polytetrahydrofuran diol is used instead of carbon dioxide-based polyol in this Comparative Example 3, and the hydroxyl value of polytetrahydrofuran diol is 54.7-57.5 mgKOH / g, the molecular weight is 1950-2050, and it is selected from PTMEG2000 of Shandong Mobai Chemical.

[0109] After testing, the tensile strength of Comparative Example 3 was 33.7 MPa, the elongation at break was 597.5%, the heat deformation temperature was 112°C, the water absorption was 0.24%, and the oxygen index was 34.8.

[0110] Comparative Example 4: The polyurethane composite material of Comparative Example 4 has the same raw materials and preparation method as those in Example 1, with specific reference to Example 1, except that no acrylic rubber is added in this Comparative Example 4, and the added amount of the POSS-terminated polyurethane resin is 92 parts.

[0111] After testing, the tensile strength of Comparative Example 4 was 38.6 MPa, the elongation at break was 780.9%, the heat deformation temperature was 110°C, the water absorption was 0.29%, and the oxygen index was 35.2.

[0112] Outer sheath: flame retardant and corrosion resistant PUR composite material.

[0113] Example 2, the flame retardant and corrosion resistant PUR composite material is made of the following raw materials in parts by mass: 70 parts of polycarbonate type waterborne polyurethane resin, 30 parts of modified polyurethane acrylate, 8 parts of silicone resin microspheres (i.e., polymethylsilsesquioxane), 15 parts of maleic anhydride grafted TPU, 4.5 parts of pentaerythritol triallyl ether, 30 parts of a second flame retardant, 4.8 parts of a smoke suppressant, 2.5 parts of a second antioxidant, 1.6 parts of a second anti-aging agent, and 1.8 parts of a second lubricant.

[0114] The raw materials, raw material models, and preparation process of the flame-retardant and corrosion-resistant PUR composite material are all described in the above specific implementation manner. Please refer to the above description for details.

[0115] Comparative Example 5, the PUR composite material of Comparative Example 5 is prepared by the same method as that in Example 2, with specific reference to Example 2, except that in Comparative Example 5, a polyether type waterborne polyurethane resin is used instead of a polycarbonate type waterborne polyurethane resin, wherein the polyether type waterborne polyurethane resin is selected from the waterborne polyurethane WPU-2616 of Return to Zero New Materials.

[0116] Comparative Example 6: The preparation method of the PUR composite material of Comparative Example 6 is the same as that of Example 2, with specific reference to Example 2. The difference is that in Comparative Example 6, epoxy acrylate is used instead of modified polyurethane acrylate, wherein the epoxy acrylate is selected from Allnex, and the model is EBECRYL1200.

[0117] Comparative Example 7: The preparation method of the PUR composite material of Comparative Example 7 is the same as that of Example 2, with specific reference to Example 2, except that silicone resin microspheres are not added in this Comparative Example 7.

[0118] Comparative Example 8: The preparation method of the PUR composite material of Comparative Example 8 is the same as that of Example 2, with specific reference to Example 2, except that polydimethylsiloxane (selected from Dow Corning DC-100) is used in place of the silicone resin microspheres in Comparative Example 8.

[0119] The flame-retardant and corrosion-resistant PUR composite materials prepared in the above Example 2 and Comparative Examples 5-8 were made into samples for performance testing, as shown in the following Table 1.

[0120] Table 1 Performance test results of flame retardant and corrosion resistant PUR composite materials

[0121]

[0122] It can be seen from the experimental results in Table 1 above that the flame retardant and corrosion resistant PUR composite material of the present invention has high mechanical strength, chemical stability, waterproofness, flame retardancy and high temperature resistance.

[0123] Application Example 1: A waterproof and corrosion-resistant optoelectronic composite cable is manufactured by the preparation method in the above specific embodiment. The raw materials and structure are as described in the specific embodiment, and the outer diameter of the optical unit is 4.0 mm, the thickness of the first protective sleeve is 0.5 mm, and the thickness of the aramid braided layer is 0.5 mm. The thickness of the second protective sleeve is 0.5 mm; the outer diameter of the electrical unit is 3.0 mm, and the thickness of the insulating layer is 1.0 mm; the aramid yarn uses 10000 dtex aramid; the wall thickness of the inner protective layer is 0.8 mm; the wall thickness of the water-blocking layer is 0.6 mm; the wall thickness of the anti-corrosion layer is 1.2 mm; and the wall thickness of the outer sheath is 2.0 mm.

[0124] The preparation methods of the waterproof, high temperature resistant and insulating polyurethane composite material and the flame retardant and corrosion resistant PUR composite material are respectively referred to Example 1 and Example 2.

[0125] Application Example 2: A waterproof and corrosion-resistant optoelectronic composite cable is manufactured by the preparation method in the above specific embodiment. The raw materials and structure are as described in the specific embodiment, and the outer diameter of the optical unit is 4.0 mm, the thickness of the first protective sleeve is 0.5 mm, and the thickness of the aramid braided layer is 0.5 mm. The thickness of the second protective sleeve is 0.5 mm; the outer diameter of the electrical unit is 3.0 mm, and the thickness of the insulating layer is 1.0 mm; the aramid yarn uses 10000 dtex aramid; the wall thickness of the inner protective layer is 0.8 mm; the wall thickness of the water-blocking layer is 0.6 mm; the wall thickness of the anti-corrosion layer is 1.2 mm; and the wall thickness of the outer sheath is 2.0 mm.

[0126] Among them, the preparation methods of the waterproof, high temperature resistant and insulating polyurethane composite material and the flame retardant and corrosion resistant PUR composite material refer to Comparative Example 1 and Comparative Example 7 respectively.

[0127] Application Example 3: A waterproof and corrosion-resistant optoelectronic composite cable is manufactured by the preparation method in the above specific embodiment. The raw materials and structure are as described in the specific embodiment, and the outer diameter of the optical unit is 4.0 mm, the thickness of the first protective sleeve is 0.5 mm, and the thickness of the aramid braided layer is 0.5 mm. The thickness of the second protective sleeve is 0.5 mm; the outer diameter of the electrical unit is 3.0 mm, and the thickness of the insulating layer is 1.0 mm; the aramid yarn uses 10000 dtex aramid; the wall thickness of the inner protective layer is 0.8 mm; the wall thickness of the water-blocking layer is 0.6 mm; the wall thickness of the anti-corrosion layer is 1.2 mm; and the wall thickness of the outer sheath is 2.0 mm.

[0128] Among them, the preparation methods of the waterproof, high temperature resistant and insulating polyurethane composite material and the flame retardant and corrosion resistant PUR composite material refer to Comparative Example 3 and Comparative Example 5 respectively.

[0129] It is worth noting that the thickness differences of each layer in Application Examples 1-3 are all within a reasonable range.

[0130] The performance of the waterproof and corrosion-resistant optoelectronic composite cables produced in the above application examples 1-3 was tested, and the test results are shown in Table 2.

[0131] It can be seen from the test data of Application Examples 1-3 that the waterproof and corrosion-resistant optoelectronic composite cable of the present invention, starting from the perspective of optimizing the formulations of various cable components and the inner protective layer, outer sheath, etc., fully utilizes the synergistic effect between various components and components, overcomes the shortcomings described in the background technology, and the product has a simple structure, easy production, a wide range of applications, and low cost, and has the characteristics of excellent flame retardancy, excellent electrical properties, good mechanical properties, strong corrosion resistance, high temperature resistance, etc.

[0132] Table 2 Cable performance test results

[0133]

[0134] The technical features of the above embodiments may be combined arbitrarily. To make the description concise, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0135] The above embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present invention. It should be pointed out that, for those of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention.

Claims

1. A waterproof and corrosion-resistant optoelectronic composite cable, comprising a cable core, an aramid yarn (7), an inner protective layer (8), a water-blocking layer (9) and an outer sheath (11), wherein the cable core comprises an optical unit and an electrical unit, and wherein: The optical unit comprises an optical fiber (2) and a protective sheath wrapped around the optical fiber (2); the electrical unit comprises a conductor (1) and an insulating layer (3) wrapped around the conductor (1); the aramid yarn (7) is spirally twisted with the cable core and is extruded with an inner protective layer (8); the inner protective layer (8) is wrapped with a water-blocking layer (9); the water-blocking layer (9) is coated with an anti-corrosion layer (10); the anti-corrosion layer (10) is coated with an outer sheath (11); The protective sleeve comprises a first protective sleeve (4), an aramid braided layer (5) and a second protective sleeve (6); the first protective sleeve (4) encloses the optical fiber (2), the first protective sleeve (4) is coated with the aramid braided layer (5), and the aramid braided layer (5) is coated with the second protective sleeve (6); The inner protective layer (8) is a waterproof, high temperature resistant and insulating polyurethane composite material; The waterproof and high temperature resistant insulating polyurethane composite material is made of the following raw materials in parts by weight: 50-70 parts of POSS end-capped polyurethane resin, 15-30 parts of acrylic rubber, 5-10 parts of ethylene-vinyl acetate copolymer, 0.5-3 parts of silane coupling agent, 5-10 parts of first flame retardant, 2.5-4 parts of first antioxidant, 0.8-1.5 parts of first anti-aging agent, and 0.5-1.5 parts of first lubricant; The outer sheath (11) is made of a flame-retardant and corrosion-resistant PUR composite material; The flame-retardant and corrosion-resistant PUR composite material is made of the following raw materials in parts by mass: 60-80 parts of polycarbonate type waterborne polyurethane resin, 20-40 parts of modified polyurethane acrylate, 5-10 parts of silicone resin microspheres, 10-20 parts of maleic anhydride grafted TPU, 3-5 parts of pentaerythritol triallyl ether, 20-40 parts of a second flame retardant, 4-6 parts of a smoke suppressant, 2-5 parts of a second antioxidant, 1.2-1.8 parts of a second anti-aging agent, and 1.5-2.5 parts of a second lubricant.

2. The waterproof and corrosion-resistant optoelectronic composite cable according to claim 1, characterized in that: The preparation method of the POSS terminated polyurethane resin comprises the following steps: S1. Place carbon dioxide-based polyol and propylene carbonate in a container, keep the temperature at 120±5°C under vacuum for 1-2h, then release the vacuum and introduce nitrogen, cool to 80±5°C, add isophorone diisocyanate, keep the temperature for 1-2h, then add an organic tin catalyst, and heat to 100±5°C for 2-5h to obtain a polyurethane prepolymer; S2. Add 4,4'-methylenebis(2-ethyl)aniline to the above polyurethane prepolymer, cool to 90±5°C and continue the reaction for 2-4h, then cool to 70±5°C, add cage-type polysilsesquioxane-hydroxyl group and keep warm for 2-5h, cool naturally to room temperature, and evacuate for 10±2min to obtain POSS-terminated polyurethane resin.

3. The waterproof and corrosion-resistant optoelectronic composite cable according to claim 2, characterized in that: The carbon dioxide-based polyol has a hydroxyl value of 34-59 mgKOH / g and a functionality of 2-3.

4. The waterproof and corrosion-resistant optoelectronic composite cable according to claim 3, characterized in that: The molar ratio of -NCO in the isophorone diisocyanate to -OH in the carbon dioxide-based polyol is (2.5-3.5): 1; The amount of propylene carbonate added is 15-30% of the mass of the carbon dioxide-based polyol; The amount of the organotin catalyst added is 0.04-0.10% of the total mass of the isophorone diisocyanate and the carbon dioxide-based polyol; The amount of 4,4'-methylenebis(2-ethyl)aniline added is 1.5-3.2% of the total mass of the isophorone diisocyanate and the carbon dioxide-based polyol; The mass ratio of the cage-type polysilsesquioxane-alcoholic hydroxyl group to the isophorone diisocyanate is (0.2-0.4):

1.

5. The waterproof and corrosion-resistant optoelectronic composite cable according to claim 1, characterized in that: The silane coupling agent is any one or more of vinyl trimethoxy silane, aminopropyl triethoxy silane or isobutyl triethoxy silane; The first flame retardant is any one or more of magnesium hydroxide, aluminum hydroxide, antimony trioxide, zinc borate or polyphosphate; The first antioxidant is any one or more of antioxidant 1010, antioxidant 168 or antioxidant B900; The first anti-aging agent is any one of UV531, UV1300 or UV1240; The first lubricant is any one of zinc stearate, magnesium stearate or calcium stearate.

6. The waterproof and corrosion-resistant optoelectronic composite cable according to claim 1, characterized in that: The second flame retardant is composed of ammonium polyphosphate AP417, magnesium hydroxide and aluminum hydroxide in a mass ratio of (1-1.5): (1.5-3): (1.5-3); The smoke suppressant is a halogen-free flame retardant carbon-forming agent FR501; The second antioxidant is composed of antioxidant 1135 and antioxidant 168 in a mass ratio of 2:1; The second anti-aging agent is composed of UV531 and UV119 in a mass ratio of 1:3; The second lubricant is one or more of calcium stearate, zinc stearate, organic montmorillonite or hydrogenated silicone oil.

7. The waterproof and corrosion-resistant optoelectronic composite cable according to claim 1, characterized in that: The insulating layer (3) is made of 90-degree insulation grade soft polyvinyl chloride plastic; The water-blocking layer (9) is a halogen-free, non-corrosive polyester non-woven water-blocking tape; The anti-corrosion layer (10) is a waterproof polyurethane anti-corrosion tape, on which a siloxane coating is applied, and the thickness of the siloxane coating is 10-20% of the thickness of the waterproof polyurethane anti-corrosion tape; The first protective cover (4) and the second protective cover (6) are both made of LSZH cable material.

8. The waterproof and corrosion-resistant optoelectronic composite cable according to claim 7, characterized in that: The siloxane coating is composed of raw materials of polydimethylsiloxane, amino silicone oil, triethoxysilane and n-hexane in a mass ratio of (5-7): (2-3): (0.1-0.2): (1-2).

Citation Information

Patent Citations

  • A highly flexible insulating sheath material for transformers and its preparation method

    CN103509302B

  • Thermoplastic polyurethane elastomer of rolling-level and high temperature resistance as well as preparation method thereof

    CN108912299A

  • Nonhalogenated Flame Resistant Cable

    US20080105454A1

  • Polyethylene blend composition

    US20200148865A1